An optimized lentiviral vector system for conditional RNAi and efficient cloning of microRNA embedded short hairpin RNA libraries. (September 2017) - Adams, Felix F.; Heckl, Dirk; Hoffmann, Thomas; Talbot, Steven R.; Kloos, Arnold; Thol, Felicitas; Heuser, Michael; Zuber, Johannes; Schambach, Axel; Schwarzer, Adrian
Abstract: RNA interference (RNAi) and CRISPR-Cas9-based screening systems have emerged as powerful and complementary tools to unravel genetic dependencies through systematic gain- and loss-of-function studies. In recent years, a series of technical advances helped to enhance the performance of virally delivered RNAi. For instance, the incorporation of short hairpin RNAs (shRNAs) into endogenous microRNA contexts (shRNAmiRs) allows the use of Tet-regulated promoters for synchronous onset of gene knockdown and precise interrogation of gene dosage effects. However, remaining challenges include lack of efficient cloning strategies, inconsistent knockdown potencies and leaky expression. Here, we present a simple, one-step cloning approach for rapid and efficient cloning of miR-30 shRNAmiR libraries. We combined a human miR-30 backbone retaining native flanking sequences with an optimized all-in-one lentiviral vector system for conditional RNAi to generate a versatile toolbox characterized by higher doxycycline sensitivity, reduced leakiness and enhanced titer. Furthermore, refinement of existing shRNA design rules resulted in substantially improved prediction of powerful shRNAs. Our approach was validated by accurate quantification of the knockdown potency of over 250 single shRNAmiRs. To facilitate access and use by the scientific community, an online tool was developed for the automated design of refined shRNA-coding oligonucleotides ready for cloning into our system. Graphical abstract: